Efektivitas Komunikasi Dakwah Digital Melalui Media TikTok Dalam Meningkatkan Pengamalan Agama Masyarakat Muslim Di Kelurahan Tanjung Mulia Medan Deli - Rusydi Aulia Siregar; Muktarruddin Muktarruddin (STAI Bumi Silampari, 2025)
This study aims to analyze the effectiveness of digital preaching (dakwah) using TikTok in enhancing religious practices among Muslim communities in Tanjung Mulia Medan Deli. A descriptive-correlational quantitative approach was employed, with data collected from 350 purposively sampled participants through structured questionnaires. Statistical analysis using Spearman’s correlation and linear regression revealed a significant positive relationship between digital dakwah access intensity and religious practice levels (? = 0.482; p < 0.001), contributing 23.2% of the variance (R² = 0.232). Key supporting factors included visual content quality (62.3%), stable internet infrastructure (78%), and collaborations between preachers and local influencers (34%), while major barriers were advertisement distractions (57.1%) and non-contextual material (28.6%). A unique